Sort by

- Relevance
- |Time

You want us to do that without first defining a,

**k**,**c**, or d? Followup: Your definitions answer your question...1 Answers · Science & Mathematics · 22/09/2018

The x-intercept occurs when y = 0 -

**k**/**c**= log_a(d(x - h)) d(x - h) = a^(-**k**/**c**) x = [a^(-**k**/**c**)]/d + h1 Answers · Science & Mathematics · 15/11/2015

...(m+1+k-1,k-1) = (induction for the first part) = C(m+k,

**k**) +**C**(m+k,k-1) = formulas = (m+k)!/[k!m!] + (m+k)!/[(k-1)!(m+1)!] = [(m+k)!*(m...1 Answers · Science & Mathematics · 09/04/2008

dT/dt =

**k**(**C**- T) ∫ dT / (C - T) = ∫ k dt - ln |C - T...6 Answers · Science & Mathematics · 26/06/2008

...definition of the binomial coefficient, and rearrange factors as necessary. C(n+k,

**k**)**C**(n, k) = ((n+k)!/(k! n!)) * (n!/(k! (n-k)!)) = (n+k)!/(k! k! (n-k)!) = ((n+k)!/((n-k...2 Answers · Science & Mathematics · 02/10/2014

**K**-**C**-C the signs of -(+4), and we have: -3 + (-4) = -7 I hope this helps!2 Answers · Science & Mathematics · 09/04/2011

Using the binomial theorem (sqrt(2)-1)^

**k**=**C**sqrt(2) - D where C and D ...1) = Csqrt(2) - D then (sqrt(2)-1)^**k**= -(**C**+D)sqrt(2) + (2C+D) If...2 Answers · Science & Mathematics · 30/10/2008

...any duplicate numbers in Step 2. That will be: n((T ∩

**K**) ∪**C**) I think this is what you asked for. forming.1 Answers · Science & Mathematics · 21/02/2017

Repeatedly apply the identity C(n,

**k**) =**C**(n-1,**k**) +**C**(n-1, k-1). [This is easy to establish by ...2 Answers · Science & Mathematics · 24/03/2012

... A X K Z K N J J

**K****C**E X Q I Z V If you don t know the...1 Answers · Science & Mathematics · 01/02/2016